2022
DOI: 10.1002/jcop.22901
|View full text |Cite
|
Sign up to set email alerts
|

The role of sense of community in improving the health‐related quality of life among Black Americans

Abstract: Black Americans have the lowest life expectancy and health‐related quality of life (HRQoL; a strong predictor of premature mortality) of any racial/ethnic group in the United States. Low rates of physical activity and engagement in healthy eating are two known contributors to low HRQoL. Black Americans are more likely to live in environments that inhibit engagement in these two contributors. The present study examined sense of community as a buffer against the adverse effects of low physical activity and healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…These findings align with the stress-buffering role that community belonging plays in mitigating stressful experiences among socioeconomically disadvantaged groups like immigrants and racial/ethnic minorities. [52][53][54][55][56] However, these results also raise questions as to why the moderating effects of community belonging varied based on specific outcomes. Only one Canadian study, to the best of the author's knowledge, has evaluated the moderating potential of community belonging among sexual minority individuals: Pakula and colleagues 32 found that community belonging intensified the disparities in mood disorders but not anxiety disorders, among homosexual individuals.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…These findings align with the stress-buffering role that community belonging plays in mitigating stressful experiences among socioeconomically disadvantaged groups like immigrants and racial/ethnic minorities. [52][53][54][55][56] However, these results also raise questions as to why the moderating effects of community belonging varied based on specific outcomes. Only one Canadian study, to the best of the author's knowledge, has evaluated the moderating potential of community belonging among sexual minority individuals: Pakula and colleagues 32 found that community belonging intensified the disparities in mood disorders but not anxiety disorders, among homosexual individuals.…”
Section: Discussionmentioning
confidence: 96%
“… 47 - 51 Furthermore, multiple studies have confirmed the stress-buffering role of community belonging among immigrants and racial/ethnic minority populations. 52 - 56 Applied to the present scenario, a strong sense of community connectedness could provide a less stigmatized living environment for sexual minority individuals, facilitating more positive identity development. 32 Moreover, a strong sense of community belonging may bolster self-esteem, promote social engagement and participation, and foster health-enhancing behaviors such as a balanced diet and regular physical activity among sexual minority individuals.…”
mentioning
confidence: 96%
“…This research finding is different from the hypothesis of this study, and from previous theories and research findings that group interaction factors may improve the quality of life of individual employees by reducing stress levels at work. 81 , 82 What is the reason? From the perspective of the characteristics of the police organization, in police groups similar to military organizations, the efficiency in job execution and task completion are the most important aspects of police organizations.…”
Section: Discussionmentioning
confidence: 99%
“…See Supplemental File 1 for the PRISMA-ScR checklist. Prior to extraction and synthesis, the protocol was registered with and published by PROSPERO, an international database of systematic reviews (Wippold et al, 2021b). The authors collaborated with a research librarian at the authors' institution to ensure a comprehensive search strategy.…”
Section: Methodsmentioning
confidence: 99%